THE TOURISM INDUSTRY IN THE ASPECT OF MARKETING MANAGEMENT - khuzaini khuzaini; M Irpan; A.S Kartika Husain (Jurnal Terapung : Ilmu - Ilmu Sosial, 2024)
AbstractThe tourism industry is a very important sector in the global economy, and marketing management plays a crucial role in the success of the tourism business. This study aims to analyze the main aspects of marketing management in the tourism industry. This study uses a descriptive-analytical approach by analyzing related literature and case studies in the tourism industry. Some of the main aspects of marketing management discussed include market segmentation, targeting and positioning; product development and innovation; promotion and marketing communications; and managing customer relationships. The research results show that effective market segmentation enables tourism companies to identify the right target groups and develop relevant marketing strategies. In addition, product development and innovation are important factors in meeting the changing needs and preferences of consumers. Effective promotion and marketing communications play an important role in introducing tourism destinations to potential tourists and influencing their decisions. In addition, managing customer relationships through positive experiences and good service can build long-term customer loyalty. This research provides a better understanding of the importance of marketing management in the tourism industry. The results of this research can serve as a guide for tourism companies in planning and implementing effective marketing strategies to achieve competitive advantage and sustainable business growth.Keywords: Industry, Tourism, Management, Marketing, Business.